Reading the Malappuram Debate: Postcolonial State and the Ethics of Place - Mohamed Shafeeq K. (SubVersions, 2014)
The district of Malappuram was formed on 16 th June 1969. Its Muslim majority demographics led to intense debates and agitation in the state, with each side accusing the other of communalism and partisanship. This paper is an exploration of the discussions as it happened in the Kerala Legislative Assembly. The paper argues that the violence of the postcolonial state vis- à-vis defining a politics of place within the state is in its legitimizing the concepts of governmentality and sovereignty as the only modes in which a politics of place can be thought of. The paper argues then for a politics which will account for notions of a communitarian space that can be expressed outside the matrix of governmentality and sovereignty